Prognostic Prediction Value of qSOFA, SOFA, and Admission Lactate in Septic Patients with Community-Acquired Pneumonia in Emergency Department - Haijiang Zhou; Tianfei Lan; Shubin Guo (Emergency Medicine International)
Background. Community-acquired pneumonia (CAP) is a leading cause of sepsis and common presentation to emergency department (ED) with a high mortality rate. The prognostic prediction value of sequential organ failure assessment (SOFA) and quick SOFA (qSOFA) scores in CAP in ED has not been validated in detail. The aim of this research is to investigate the prognostic prediction value of SOFA, qSOFA, and admission lactate compared with that of other commonly used severity scores (CURB65, CRB65, and PSI) in septic patients with CAP in ED. Methods. Adult septic patients with CAP admitted between Jan. 2017 and Jan. 2019 with increased admission SOFA ≥ 2 from baseline were enrolled. The primary outcome was 28-day mortality. The secondary outcome included intensive care unit (ICU) admission, mechanical ventilation, and vasopressor use. Prognostic prediction performance of the parameters above was compared using receiver operating characteristic (ROC) curves. Kaplan–Meier survival curves were compared using optimal cutoff values of qSOFA and admission lactate. Results. Among the 336 enrolled septic patients with CAP, 89 patients died and 247 patients survived after 28-day follow-up. The CURB65, CRB65, PSI, SOFA, qSOFA, and admission lactate levels were statistically significantly higher in the death group (P<0.001). qSOFA and SOFA were superior and the combination of qSOFA + lactate and SOFA + lactate outperformed other combinations of severity score and admission lactate in predicting both primary and secondary outcomes. Patients with admission qSOFA < 2 or lactate ≤ 2 mmol/L showed significantly prolonged survival than those patients with qSOFA ≥ 2 or lactate > 2 mmol/L (log-rank χ2 = 59.825, P<0.001). The prognostic prediction performance of the combination of qSOFA and admission lactate was comparable to the full version of SOFA (AUROC 0.833 vs. 0.795, Z = 1.378, P=0.168 in predicting 28-day mortality; AUROC 0.868 vs. 0.895, Z = 1.022, P=0.307 in predicting ICU admission; AUROC 0.868 vs. 0.845, Z = 0.921, P=0.357 in predicting mechanical ventilation; AUROC 0.875 vs. 0.821, Z = 2.12, P=0.034 in predicting vasopressor use). Conclusion. qSOFA and SOFA were superior to CURB65, CRB65, and PSI in predicting 28-day mortality, ICU admission, mechanical ventilation, and vasopressor use for septic patients with CAP in ED. Admission qSOFA with lactate is a convenient and useful predictor. Admission qSOFA ≥ 2 or lactate > 2 mmol/L would be very helpful in discriminating high-risk patients with a higher mortality rate.